Questionnaire-Based Pronunciation Studies: Italian, Spanish and Polish Students’ Views on their English Pronunciation - Nowacka, Marta (Research in Language, 2012)
This article is an attempt to review the most recent phonetic literature on the application of questionnaires in phonetic studies. In detail, we review the scope of pronunciation questionnaire-based surveys with respect to Polish and non-Polish students of English. In addition, this paper aims to examine European students’ beliefs and attitudes towards their own English pronunciation and is also intended to provide some arguments for or against the use of foreign-accented rather than native models of pronunciation in phonetic instruction. The data come from three groups of informants, namely: Italian, Spanish and Polish students of English. With respect to foreign, non-Polish respondents, the study was conducted at the University of Salento in Italy and the University in Vigo, Spain within the framework of the Erasmus Teacher Mobility Programme in two consecutive academic years: i.e. 2010/2011 and 2011/2012. As regards Polish respondents, our research involved subjects from six different tertiary schools, i.e. five universities and one college, located in various parts of Poland. On balance, the results of our study give an insight into the phonetic preferences of adult European advanced students of English with reference to the importance of good native-like pronunciation, the aims of pronunciation study, factors contributing to phonetic progress and their self-study pronunciation learning strategies. Our findings point to the fact that students of English wish to speak with good pronunciation, set a high native-like standard for themselves, report having benefited from their phonetic instruction and exposure to native English and that they work on their pronunciation by means of various, mostly cognitive, strategies. Rather than casting new light on teaching pronunciation, the outcome of this study is consistent with the findings of other research on foreign students’ choice of preferred pronunciation model, which is undeniably native rather than foreign-accented.